Acid‐Induced Degradation and Ancillary Ligand Replacement of Biscyclometalated Iridium(III) Complexes. Issue 5 (3rd April 2013) - Zhou, Yuyang; Li, Wanfei; Liu, Yang; Zhou, Ming
Abstract Three biscyclometalated iridium(III) complexes with three different ancillary ligands have been investigated with respect to the final products of acid‐induced transformation in coordinating or non‐coordinating solvents. All of these complexes, represented as [Ir(LC^N)2LO^O] and [Ir(LC^N)2LN^O], are susceptible to acid attack, followed by the departure of the ancillary ligand, LO^O or LN^O. Depending on the coordinating ability of the solvent molecule and whether or not a coordinating anion exists, the final product will be either a solvento complex or a dichloro‐bridged iridium(III) dimer. Although coexistence of the solvento complex and dichloro‐bridged iridium(III) dimer was observed under certain conditions, the conversion of the solvento complex into the dichloro‐bridged iridium(III) dimer has been proven.